Effects of preoperative carprofen on cardio-respiratory, hormonal and metabolic stress response in calves during umbilical surgery under isoflurane inhalation anaesthesia. (October 2016) - Schulze, I.; Poos, E.M.; Meyer, H.; List, A.K.; Kaestner, S.B.R.; Rehage, J.
Highlights: The effect of preoperative carprofen on anti-nociception during umbilical surgery is examined. A lower cortisol level indicates beneficial effects of NSAID pre-treatment before surgery. Preoperative administration of carprofen leads to a lower systemic vascular resistance. The applied anaesthetic protocol showed a reliable analgesia. Abstract: The aim of this study was to examine the effects of preoperative carprofen on the cardiorespiratory, hormonal and metabolic stress response during umbilical surgery under isoflurane anaesthesia combined with local anaesthesia, in calves. A randomised, blinded experimental study was conducted in 24 calves. Carprofen ( n = 12; 1.4 mg/kg) or physiological saline solution (controls; n = 12) was administered 1 h prior to surgery. Anaesthesia was induced with xylazine (0.1 mg/kg, IM) and, after the onset of sedation (i.e. after 5–8 min), ketamine was administered (2 mg/kg, IV). Anaesthesia was then maintained with isoflurane (ISO) in oxygen to effect and completed by infiltration of the incision line with 20 mL of 2% procaine. Cardiorespiratory, endocrine and metabolic parameters were examined before, during and after surgery at short intervals. In both groups, anaesthesia appeared adequate for the surgical intervention. Heart rate, stroke index and arterial blood pressure were significantly elevated after the onset of surgery. Oxygen partial pressure and oxygen delivery increased, while the oxygen extraction ratio decreased intraoperatively, ensuring sufficient oxygen supply. In the control group, the mean surge in serum cortisol concentrations tended to be higher ( P = 0.089) and systemic vascular resistance (SVR) was significantly greater ( P < 0.05) than in the carprofen group during surgery. In conclusion, the anaesthetic protocol used in this study induced reliable analgesia in both groups. The lower serum cortisol levels and SVR may indicate a reduced surgical stress response in calves undergoing umbilical surgery under ISO anaesthesia after administering carprofen preoperatively.